The impacts of fans' sincerity perceptions and social media usage on attitude toward sponsor - (:unkn) unknown (EMERALD GROUP PUBLISHING LTD, 2016)
Purpose - The purpose of this paper is to contribute understanding of sponsorship by examining the impacts of team attachment, perceived fit, perceived sincerity and sport team focussed social media consumption on attitudes toward sponsor and intentions to purchase products of sponsor. Design/methodology/approach - Data were collected through survey method. The questionnaires were completed by 310 fans in the arena before the beginning of a professional football game in Istanbul, Turkey. The hypothesized model was tested by using structural equation modeling. Findings - The results reveal that sport consumers who see a fit between the sponsor and sport team are more likely to believe that the sponsor's motives are sincere and sincerity perceptions, in turn, positively influence attitudes toward sponsor and intentions to purchase sponsor's products. The research also provides empirical evidence for the direct impacts of perceived fit and fans' usage of social media for receiving team-related information on purchase intentions. Practical implications - Findings of the current study suggest that sponsor firms should communicate their sincere motives, their fit with the sponsored sport team and be present and active on social media accounts of the sport team in order to leverage their sponsorship. Originality/value - This study showed that sport team focussed social media consumption has a positive influence on intentions to purchase products of sponsor in an emerging market setting, Turkey, which promises growth in sports market and sponsorship.
Keywords: Turkey; Social media; Sport marketing; Purchase intention; Sponsorship; Sport sponsorship; BRAND; IDENTIFICATION; CONSUMPTION; CONGRUENCE; INTENTIONS; HIERARCHY; CONGRUITY; CONTEXT; MODEL; FIT